The Impact of School Principals on Graduate Quality Through Character Education Initiatives - Sanjani , M Aqil Fahmi (Al-Qalam Institue, 2024)
This article aims to delve into the multifaceted process of character education with principals, focusing on the pivotal roles of teachers and educational staff. Drawing from qualitative research and philosophical insights, we examine three critical stages of character development: building teacher character with principal leadership, fostering the character of educational staff, and nurturing student character in madrasah. Data were obtained through interviews, documentation, and observation. Through a comprehensive analysis, we underscore the significance of teacher character as the cornerstone of character education, emphasizing the importance of embodying values such as integrity, morality, and trustworthiness. By synthesizing research findings and philosophical perspectives, this article aims to provide valuable insights and recommendations for enhancing character education in madrasas, ultimately fostering the growth of students who exemplify integrity, compassion, and resilience in their everyday lives. Disciplined attitudes and democratic leadership are certainly an adequate basis for building the quality of graduates, and this is built through cultural and character education as national education goals.